Quality of Online Information Regarding High-Risk Pregnancies. Issue 12 (December 2021) - Lee, Shin-Young; Lee, Seonah
Abstract : Health information on the Internet can have a direct effect on healthcare decision-making. However, the quality of information online has seldom been evaluated. This study aimed to assess the quality of online information on high-risk pregnancies provided by English and Korean Web sites. Through a Google search, 30 English and 30 Korean Web sites were selected on January 2 and 3, 2020, respectively, and assessed using DISCERN, a Journal of the American Medical Association, and Health On the Net Foundation code questionnaires. The data assessed were analyzed using descriptive and nonparametric statistical tests. Overall, the information provided by the English Web sites presented higher-quality information than the Korean Web sites. Most Web sites did not provide the sources of the information presented on their Web sites, meet the Journal of the American Medical Association criteria, or provide information on complementarity. Based on our results, nurses need to be competent in assessing the quality of Web sites and the health information presented there, and nursing students need to be prepared to do so as well. Nurses are responsible for educating their patients about the possibility of incorrect information provided by Internet Web sites and informing their patients about reliable Web sites, thus assisting them to make informed decisions regarding their health. Abstract : Supplemental digital content is available in the text.